Applicability of Mn-Mg binary oxide nanoparticles for the adsorptive removal of copper and zinc from aqueous solution. (2021) - Ullah Khan, Saif; Khalid, Mohd; Zaidi, Rumman; Haq Farooqi, Izharul; Azam, Ameer; Ayub, Sohail
Abstract: In the present study, synthesis of a novel Mn-Mg binary metal oxide was carried out using facile co-precipitation method for the possible adsorption of copper and zinc from aqueous medium. The prepared adsorbent was characterised to explore the morphology and structure using XRD and SEM. Experimental studies at batch scale were carried out examining the consequence of varying dosage of adsorbent, initial metal concentration, pH of solution and contact time on the adsorptive removal of both copper and zinc. The efficiency was found to increase with increasing dosage of adsorbent (0.1–0.5 g/L) and inversely with initial chromium concentration (10–50 ppm). Adsorption was found increasing with pH shifting from acidic to basic pH range. Adsorption isotherms plotted indicated freundlich model to be fitting better along with pseudo 2nd order kinetics.